Experience of rectosacropexy in treatment of patients with rectum prolapse - A. Yu. Titov; O. M. Biryukov; O. Yu. Fomenko; A. A. Tikhonov; M. A. Voynov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze authors’ experience of rectosacropexy results at prolapse of the rectum. Material and methods. Original study included 137 patients who underwent surgery for prolapse of rectum in the State scientific center of coloproctology from January, 2007 to December, 2013. The main group have included 60 patients (43,8%) who had rectosacropexy, control group included 77 patients (56,2%) after back loop rectopexy.Results. Control examination was carried out in 24 patients (40%) of the main and in 26 patients (33,8%) of the control group. Average time of follow-up was respectively 9,8±2,0 months and 34,2±17,8 months. Relapse was diagnosed in 2 patients (7,6%) after back loop rectopexy. After surgical treatment of rectal prolapse statistically significant improvement of anal sphincter pressure was diagnosed in both groups at I and II degree of sphincter insufficiency. Application of rectosacropexy corrects pelvic floor descent syndrome and evacuatory function of the rectum. No deterioration of large intestinal transit after rectosacropexy was revealed (р>0,05). After back loop rectopexy deterioration of large intestinal emptying (р<0,05) was significant.Conclusions. Rectosacropexy is effective method of rectum prolapse treatment and improves function of anal sphincter in postoperative period, corrects pelvic floor descent syndrome and cause no constipation.